Effects of Different Enzymatic Hydrolyses of Mutton Tallow on the Aroma Characteristics of the Maillard Reaction of Xylose–Cysteine Based on GC‐MS, E‐Nose, and Statistical Analysis. Issue 3 (23rd December 2019) - Ma, Xueping; Zhan, Ping; Tian, Honglei; Wei, Zhisheng; Wang, Peng
Abstract: Solid‐phase micro extraction/gas chromatography‐mass spectrometry (SPME/GC‐MS), electronic nose (E‐nose), and descriptive sensory analysis (DSA) are used to evaluate the changes in aroma characteristic of six mutton tallow flavor (MF) samples prepared from xylose–cysteine with mutton tallow or different enzymatic hydrolysis mutton tallow (EM) with different enzymes. 61 compounds are identified by GC‐MS as crucial compounds contributing to the MF for the evaluation of the sensory characteristics of MFs. Most of the volatiles, including aldehydes, alcohols, furans, and thiophenes, decrease because of the addition of EMs. The EM with lipase MER produces more appropriate volatile compounds through the Maillard reaction than the other samples. Five attributes are selected for the appraisal of MFs. DSA results show a remarkable difference in sensory attributes among the MFs. MF5 has the strongest aroma in the muttony and meaty flavors, and the weakest in the burnt and off‐flavor. Further investigation of the six MFs is conducted based on the volatile compounds evaluated by E‐nose. The results of the correlation analysis among the volatile compounds and the DSA confirm that EM with lipase MER may be an appropriate precursor for MF's sensory characteristics. Practical Applications : Moderate lipid oxidation is a prerequisite to achieving a characteristic flavor. However, over‐treatment will lead to an undesirable smell. The thermal method requires high temperature and is difficult to control, and the resulting natural meat flavor needs improvement. A possible solution is to use enzymes to make a difference in the molecular weight of the enzymatically hydrolyzed fragments. To achieve controlled enzymatic hydrolysis of a fragment, the correct selection of enzyme is an important step. The present study helps elucidate how lipids contribute to the formation of meat flavor, thereby providing guidance for the preparation of thermal reaction meat flavor. Abstract : The compositions and contents of volatile compounds in mutton tallow flavor (MF) are significantly different. Thus, e‐nose can be used to evaluate and confirm the difference of MF. The partial least squares regression is applied to ensure the relationship between sensory attributes, volatiles, and MF.